The Plebs, 1948 (London, 1948)
1948 1945-1951 "The Plebs, 1948" [BW0105], 1948, Trades Union Congress The front page from the September 1948 issue of 'The Plebs' magazine, published by the National Council of Labour Colleges, carries an article critical of a TUC report on the rationalisation of trade union education.